Dysmenorrhea Primer: Tinjauan Pustaka - Ananda Felicia Aziza; Dian Isti Angraini; Ramadhana Komala; Rika Lisiswanti (CV. Jasa Sukses Abadi, 2024)
Dysmenorrhea is a common gynecological complaint among adolescent girls and young women, characterized by disruptive menstrual pain. This condition can affect health, social relationships, as well as school and work activities. The WHO in 2017 stated that 90% of women of reproductive age worldwide experience dysmenorrhea, while in the Southeast Asia region, the prevalence reaches 50.9% in Malaysia and 64.25% in Indonesia. Dysmenorrhea can be classified into primary dysmenorrhea, which occurs without any underlying pelvic pathology, and secondary dysmenorrhea, which occurs due to pelvic pathology such as endometriosis. The severity of primary dysmenorrhea can be classified as mild, moderate, and severe using the WaLIDD Score, a tool that helps measure the intensity and impact of pain. Management of dysmenorrhea can include NSAID medications, hormonal therapy, and alternative therapies such as exercise, although their effectiveness has not been consistently proven. Most teenage girls often consider dysmenorrhea to be a normal part of a menstrual cycle. However, dysmenorrhea that does not receive proper treatment will later impact cases of endometriosis in the future. With a better understanding of the causes and management of dysmenorrhea, it is hoped that patient awareness can be increased and they can be encouraged to seek appropriate medical treatment.